2022
DOI: 10.1039/d2tb01316a
|View full text |Cite
|
Sign up to set email alerts
|

Selectivec-MYCG4 DNA recognition based on a fluorescent light-up probe with disaggregation-induced emission characteristics

Abstract: c-MYC promoter is well-known as an important oncogene, whose overexpression leads to ∼80% of all solid tumors. The four-stranded G4 present in the c-MYC promoter has been shown to play...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Notably, the LOD of SN-Cy5-S was 1.51 nM, which was lower than for the previously reported DIE probes (Table ). ,,, A Job’s plot experiment demonstrated that SN-Cy5-S and G4s combined in ratios of 1:1 or 2:1 (Figure S15), consistent with the results of the above-described nonlinear fitting.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Notably, the LOD of SN-Cy5-S was 1.51 nM, which was lower than for the previously reported DIE probes (Table ). ,,, A Job’s plot experiment demonstrated that SN-Cy5-S and G4s combined in ratios of 1:1 or 2:1 (Figure S15), consistent with the results of the above-described nonlinear fitting.…”
Section: Resultssupporting
confidence: 84%
“…Among small-molecule fluorescent probes, cyanine dyes almost dominate the research field of photography and other relevant biosensing and disease theranostics, due to their favorable optical properties (e.g., high molar extinction coefficient and adjustable absorption and fluorescence spectra) as well as high biocompatibility. However, conventional cyanine dyes exist as “always-on” fluorescent probes, which inevitably accumulate and are retained in non-target regions producing background signals, lowering the biological selectivity for bioimaging. In contrast, activatable probes can change fluorescence intensity or emission wavelength in response to specific physiological parameters, exhibiting higher signal-to-noise ratio and specificity, resulting in a lower detection limit compared to “always-on” fluorophores. Therefore, designing activatable probes based on cyanine skeletons to selectively illuminate G-quadruplex structures is essential for improving detection sensitivity, especially for in vivo imaging with high complexity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of luminescent materials coupled with the rapid evolution of optical microscopy techniques has allowed generation of valuable knowledge in the roles and functions that G4s play in cells. ,, However, in many conventional systems, fluorophores experience the phenomenon of aggregation-induced quenching (ACQ) that limits their full potential as diagnostic agents . Recently, we and others have introduced a selective G4 recognition strategy that relies on the disassembly of self-aggregated dyes, namely, disaggregation-induced emission (DIE). Dyes operating through DIE display remarkable topological/sequence selectivity , for G4s and have broad applicability in cellular systems. ,, …”
mentioning
confidence: 99%
“…Recently, we and others have introduced a selective G4 recognition strategy that relies on the disassembly of self-aggregated dyes, namely, disaggregation-induced emission (DIE). Dyes operating through DIE display remarkable topological/sequence selectivity , for G4s and have broad applicability in cellular systems. ,, …”
mentioning
confidence: 99%